Nerve growth factor‐induced migration in oral and salivary gland tumour cells utilises the PI3K/Akt signalling pathway: Is there a link to perineural invasion?. (22nd December 2019) - Alkhadar, Huda; Macluskey, Michaelina; White, Sharon; Ellis, Ian
Abstract: Objectives: The aims of this study were to investigate the role of nerve growth factor on perineural invasion in oral and salivary gland tumour cell lines and whether there is an involvement of PI3K/Akt pathway. Materials and Methods: Four cell lines were investigated: HSG and TYS (salivary gland tumours), SAS‐H1 (oral squamous cell carcinoma) and HaCaT (human skin keratinocyte). Initially, Boyden chamber assay was done to examine the effect of different concentration of nerve growth factor on cell migration. Western blot/ immunofluorescence techniques were used to investigate the phosphorylation status of the Akt pathway within the cells in response to nerve growth factor. The effect of this growth factor and the addition of an Akt inhibitor on cell morphology and migration were also examined using scatter/scratch assays. Results: Nerve growth factor triggered the PI3K/Akt pathway in oral and salivary tumour cells and induced oral and salivary tumour cell scattering and migration. Inhibitor assays confirmed that oral and salivary gland tumour cell scattering and migration is Akt dependent. Conclusions: Nerve growth factor can stimulate scattering and migration in cells derived from oral and salivary gland tumours, thereby potentially enhancing perineural invasion. Phosphorylated Akt controls cancer cell migration and scattering. Blocking the Akt pathway may inhibit cell migration and therefore perineural invasion and metastasis.